2014
DOI: 10.4067/s0717-95022014000100046
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Nutritional Induction of Type 2 Diabetes Mellitus

Abstract: SUMMARY:Type 2 diabetes mellitus (DM2) is the most common chronic metabolic disease, affecting approximately 6% of the adult population in the Western world. This condition is a major cause of cardiovascular disease, blindness, renal failure, and amputations, with increasing prevalence worldwide. The influence of obesity on type 2 diabetes risk is determined by the degree of obesity and by body fat localization, with insulin resistance (IR) being the main link between these metabolic diseases. Experimental stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…In humans and rodents, intake of a diet rich in fructose and fat produces insulin resistance (and/or hyperglycemia) and metabolic changes in tissues [2,3]. A number of structural and functional changes in the myocardium such as cardiac hypertrophy, cardiac fibrosis, and ventricular contractile dysfunction and cardiovascular remodeling are reported in high-fat high-fructose diet-fed rats [4,5].…”
Section: Introductionmentioning
confidence: 97%
“…In humans and rodents, intake of a diet rich in fructose and fat produces insulin resistance (and/or hyperglycemia) and metabolic changes in tissues [2,3]. A number of structural and functional changes in the myocardium such as cardiac hypertrophy, cardiac fibrosis, and ventricular contractile dysfunction and cardiovascular remodeling are reported in high-fat high-fructose diet-fed rats [4,5].…”
Section: Introductionmentioning
confidence: 97%
“…It is generally believed that T2DM is driven by a complex interplay of genetic factors and unhealthy lifestyle habits comprising an energy-dense "westernized" diet [10][11][12][13][14]. Hence, diet-induced rodent models of T2DM, whether alone or combined with genetic/chemical stressors, are paramount to more closely replicate human microvascular complications [15,16]. The most commonly used diets for T2DM animal research are high-fat diets (HFD), high-sugar diets (HSD), and Western diets combining both high-fat and high-sugar components (HFSD) [17].…”
Section: Introductionmentioning
confidence: 99%
“…This condition has been termed as compensatory hyperinsulinemia [45]. The previous literature has also revealed that dietary high-fat leads to promote insulin resistance and hyperinsulinemia before the development of type 2 diabetes in rodents [48][49][50]. High-fat diet-induced hyperinsulinemia or insulin resistance may occur due to a decrease in the glucose transporter, insulin receptors, and glucose metabolism [10,28].…”
Section: Discussionmentioning
confidence: 99%